Implementation of Environmental Management System (ISO 14001) in Supporting the Achievement of Corporate Sustainability Performance in the Pulp and Paper Manufacturing Industry in Indonesia - Erwin Erwin (Institut Teknologi Sains Bandung, 2021)
Objectives: This study analyses the implementation of an environmental management system based on the ISO 14001 standard, which can support corporate sustainability performance in the pulp and paper manufacturing industry in Indonesia. This study discusses the results of previous researchers related to the implementation of environmental management systems in supporting the achievement of corporate sustainability performance. Research Methodology: The research method used is a case study approach in five organizations from three pulp and paper manufacturing companies in Indonesia that have implemented environmental management systems. Collecting data through a questionnaire completed by representatives from organizations across the companies studied. Findings: Management commitment and implementation of internal audits that focus on environmental management and activities are the main factors contributing to the achievement of environmental performance. Meanwhile, the achievement of environmental performance is influence by employees' increased competence in the environmental field, programs to reduce energy consumption, and hazardous and toxic waste. Practical implications: The implementation of an environmental management system supported by an increase in environmental performance can improve the company's reputation, process efficiency and compliance with environmental regulations and requirements, that three things contribute to company performance, especially in the pulp and paper manufacturing industry. Novelty: This research contributes to the concept of a strong relationship between the implementation of environmental management systems and environmental performance in supporting the achievement of corporate sustainability performance, especially in the pulp and paper manufacturing industry in Indonesia.